Variance Component Decomposition for Growth Traits of the Bay Scallop (Argopecten irradians irradians) - Li, Hengde; Wang, Yangfan; Xing, Qiang; Zeng, Qifan; Zhao, Liang; Zhang, Yaqun; Hu, Xiaoli; Bao, Zhenmin (Frontiers in Marine Science, 2021)
The bay scallop (Argopecten irradians irradians) is one of the important shellfish species in China. Since introduced into China, only mass selection was used in the bay scallop breeding. With its expansion and shortage of mate selection, population homozygosity increased and fitness decreased. In this study, the variance components of the growth traits of the bay scallop were decomposed with genomic relationship matrices. The results showed that the genetic variations of shell height and length were mainly accounted for by the additive effects; the genetic variation of shell width was mainly caused by dominance, or dominance by dominance epistasis. The genetic variation of shell weight was accounted for by dominance. No significant directional dominance were detected for all growth traits. Cross validation for genomic prediction showed that it is not necessary to include insignificant inbreeding in the genomic prediction model, and we suggested to optimize genomic prediction model with both likelihood ratio tests and cross validation before utilization in practise.